Semiotyczno-audialne znaki radiowe a rzeczywistość przedstawiona w wybranych słuchowiskach radiowych (motyw lasu) - Bachura, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The aim of this article was to present the forest motif in selected radio plays and to suggest several possible ways of their interpretation. Here, also the attention was focused on radio play as a great work of radio art, in particular on specificity and structure of this kind, a word participation as well as an acoustic aspect which is equally important. Deliberations associated with the aspects mentioned above were shown due to exemplification. Existence of the forest has perfectly become an the educative function especially in children’s radio plays. Analyses of the radio plays have brought the reflection about the forest and nature as ostensible radio play action background. Indeed it is regular that the forest and nature inspire to deep discussion about the human soul and emotions as well as to unravel human behaviors. Furthermore, great metaphors are built on top of these meanings.